2005
DOI: 10.1111/j.0306-686x.2005.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

International Publishing Patterns: An Investigation of Leading UK and US Accounting and Finance Journals

Abstract: Research quality is often measured by the quality of the journals in which articles are published. This article looks at 1,867 articles published in six highly-rated UK and six highly-rated US academic journals from 1996 to 2000. The authors publishing in the UK journals come mainly from UK and US institutions, but just over a third come from other countries. However, almost ninety per cent of authors publishing in top US journals come from US institutions. Contributions from authors from institutions in non-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 30 publications
12
82
1
4
Order By: Relevance
“…[ Jones and Roberts (2005). This reinforces the view of Lukka and Kasanen (1996), supported by empirical evidence by Beattie and Davie (2006), that accounting remains a local discipline, with a US elite distinguishable from an emerging non-US elite.…”
Section: Comparison With Glover Et Al's (2006) Study Of Promotions Isupporting
confidence: 69%
See 1 more Smart Citation
“…[ Jones and Roberts (2005). This reinforces the view of Lukka and Kasanen (1996), supported by empirical evidence by Beattie and Davie (2006), that accounting remains a local discipline, with a US elite distinguishable from an emerging non-US elite.…”
Section: Comparison With Glover Et Al's (2006) Study Of Promotions Isupporting
confidence: 69%
“…All of these eight journals are edited and published in the US and it is well-established that UK academics find it difficult to publish in such journals (Jones and Roberts, 2005). Further, Beattie and Davie (2006) document the existence of geographically-based competing research elites (one US and one non-US) based on methodological differences.…”
Section: Specific Journals Included In Professor Promotion Portfoliosmentioning
confidence: 99%
“…This implies a high level of concentration in publication. A later study conducted by Jones and Roberts (2005) found similar results. They examined 1,867 articles published in six highly-rated UK and six highly-rated US academic journals from 1996 to 2006.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Zimmerman identificou o que, para ele, eram problemas na pesquisa em contabilidade gerencial, como, por exemplo, o fato de que os pesquisadores utilizavam métodos qualitativos e uma perspectiva indutiva, não se baseavam em uma teoria econômica, não testavam modelos, e se dedicavam muito ao processo de tomada de decisão, e não ao controle organizacional. Estas afirmações geraram várias críticas e um extenso debate sobre o futuro da contabilidade gerencial, suas limitações e potencialidades (LUFT; SHIELDS, 2002;HOPWOOD, 2002;BAXTER;CHUA, 2003;FREZATTI;JUNQUEIRA, 2009;MALMI;GRANLUND, 2009). A provocação de Zimmerman indica como houve necessidade de estímulo externo para que a comunidade sentisse necessidade de pensar e reagir.…”
Section: Prescrevendo O Futuro Da Pesquisa Empírica Em Contabilidade unclassified
“…A maioria das publicações relevantes em contabilidade gerencial na Europa provém de pesquisadores que trabalham no Reino Unido (CARMONA; GUTIERREZ;CAMARA, 1999;JONES;ROBERTS, 2005;RAFFOURNIER;SCHATT, 2010). Particularmente, o que acontece no Reino Unido em termos de contabilidade gerencial é de certa forma diferente do que acontece no resto da Europa.…”
Section: Tendênciasunclassified